Understanding perspectives and research trends in down syndrome neuropathogenesis: a bibliometric analysis - Huang, Tan; Lam, Xin-Jieh; Lim, Chong-Teik; Jusoh, Norhazlin; Fakurazi, Sharida; Cheah, Pike-See; Ling, King-Hwa (SAGE Publications Ltd, 2024)
Down syndrome (DS), characterised by compromised brain development and intellectual challenges, often manifests Alzheimer's disease (AD) -like symptoms. Utilising the Web of Science Core Collection (WOSCC) database from January 1, 2000, to July 31, 2023, we conducted a comprehensive bibliometric analysis using VOSviewer, CiteSpace, and the R package “bibliometrix.” Analyses included co-authorship, co-citation, co-occurrence, cooperative network, reference, and keyword burst citation. Analysing 5,082 papers, the U.S. demonstrated prominence with the highest number of research organisations and citations. Keyword analysis revealed promising research areas, including “Alzheimer's disease,” “development,” “inflammation,” and “neurogenesis”. This 22-year survey of the brain with trisomy 21 research unveils key trends, contributors, and focal areas in DS neuropathogenesis. Notably, Alzheimer ’s-related genes and proteins play a pervasive role in DS neuropathological processes across patients' lifespans. The study contributes foundational knowledge for advancing research and care in the DS neuropathogenesis domain.